Kontestasi Ideologi Bahasa dalam Pemilihan Presiden 2019 Pada Pola Horizontal, Vertikal, dan Individual (Contestation of Language Ideology in the 2019 Presidential Election on Horizontal, Vertical, and Individual Patterns) - M Wildan; Muhammad Saleh; Aqodiah Aqodiah (Jurusan Tadris Bahasa Indonesia, 2023)
This study aims to explain the ideological contestation of language in the 2019 Presidential Election (Pilpres) which has horizontal, vertical, and individual patterns. Data were analyzed using a narrative analysis approach to mainstream media news texts and uploads of citizens' statuses on social media. The results of the study show that the ideological contestation of language that occurred in the 2019 Presidential Election by paying attention to the facts of cebong, kampret, and kadrun languages has formed netizens to be polarized into three patterns, namely horizontal, vertical, and individual. Netizens became patterned because the three unique lexicons of the 2019 Presidential Election had been integrated into him. For this reason, polarization does not only occur during the 2019 presidential election but also after the presidential election and may even continue until the upcoming 2024 presidential election.Penelitian ini bertujuan untuk menjelaskan kontestasi ideologi bahasa dalam Pemilihan Presiden (Pilpres)Â 2019 yang berpola horizontal, vertikal, dan individual. Data dianalisis denganÂ menggunakan pendekatan naratif analisis terhadap teks pemberitaan media arus utama dan unggahan status warganet pada media sosial. Hasil penelitian menunjukkan bahwa kontestasi ideologi bahasa yang terjadi pada Pilpres 2019 dengan memperhatikan fakta bahasa cebong, kampret, dan kadrun telah membentuk warganet menjadi terpolarisasi ke dalam tiga pola, yaitu horizontal, vertikal, dan individual. Warganet menjadi terpola karena telah terintegrasinya tiga leksikon unik Pilpres 2019 itu pada dirinya. Untuk itu, polarisasi tidak hanya terjadi pada masa Pilpres 2019, tetapi juga pasca-Pilpres dan bahkan dapat berlanjut hingga Pilpres 2024 mendatang.Â